2013
DOI: 10.1097/aog.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Massive Blood Transfusion During Hospitalization for Delivery in New York State, 1998–2007

Abstract: OBJECTIVE To define the frequency, risk factors, and outcomes of massive transfusion in obstetrics. METHODS The State Inpatient Dataset for New York (1998–2007) was used to identify all delivery hospitalizations for hospitals that reported at least one delivery-related transfusion per year. Multivariable logistic regression analysis was performed to examine the relationship between maternal age, race, and relevant clinical variables and the risk of massive blood transfusion defined as 10 or more units of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
89
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 22 publications
(26 reference statements)
12
89
2
1
Order By: Relevance
“…In the current report, the primary etiologies for major obstetric hemorrhage were obstetric trauma, abnormal placentation, and uterine atony, while others reported leading causes for severe postpartum hemorrhage to be abnormal placentation, uterine atony, and placental abruption [5]. Nevertheless, comparison of this series to others is difficult because of different definitions of major obstetric hemorrhage and varying inclusion criteria.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In the current report, the primary etiologies for major obstetric hemorrhage were obstetric trauma, abnormal placentation, and uterine atony, while others reported leading causes for severe postpartum hemorrhage to be abnormal placentation, uterine atony, and placental abruption [5]. Nevertheless, comparison of this series to others is difficult because of different definitions of major obstetric hemorrhage and varying inclusion criteria.…”
Section: Discussionmentioning
confidence: 85%
“…Using these criteria, the incidence of major obstetric hemorrhage event in the current study is within the range reported for developed countries: the Scottish confidential audit of severe maternal morbidity noted a rate of 5.9/1000 births during 2011 [22] and the Canadian incidence of PPH requiring hysterectomy or transfusion was 1.04/1000 births between 1998 and 2000 [23]. A population level analysis in New York State calculated the expected incidence of C10 RBC units transfusion in facilities with delivery volume [4000 births annually as 0.8/1000 deliveries [5].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations